Tuberculose infecção entre estudantes de graduação da área da saúde : estudo de prevalência e avaliação do conhecimento - Maia, Cheila Oliveira Lima (2013)
Infection with Mycobacterium tuberculosis (TB) affects one third of the world’s population and is considered a global emergency. Research has shown an increased risk of TB among healthcare workers and students. The purpose of the study was to determine the prevalence of TB infection and evaluate the students’ knowledge of TB. A quantitative, cross-sectional study was conducted with 311 medical and nursing students from the Federal University of Ceará stratified by period. Sociodemographic information was collected, a questionnaire with basic questions on TB was administered, and the Mantoux test (MT) was performed on all participants. Two cut-off values for TB were considered: ≥5 mm (general population) and ≥10 mm (health professionals). The associations between MT results, students’ knowledge of TB and the categorical variables were submitted to the chi-square test, the chi-square test for trend and the likelihood ratio test. The mean values were compared with Student’s t test and the Kruskal-Wallis test, with the level of statistical significance set at 5% (p<0.05). Most of the participants (69.5%) were female, 67.5% were aged 20-24 years, and 90.7% had a BCG scar. The medical students and the nursing students differed with regard to socioeconomic characteristics. Only 17.4% reported receiving training in TB. The medical students were distributed over three periods: pre-clinical (30.5%), clinical (38.3%), internship/supervised curricular traineeship (31.2%). MT values of 5-9 mm and ≥10 mm were found for 38 (21.6%) and 30 (17.0%) medical students, respectively. The corresponding findings for nursing students were 21 (22.8%) and 26 (28.3%). The average MT values and standard deviation by medical course period were 3.5 ± 4.2 mm (pre-clinical) and 5.3 ± 4.5 mm (internship) (p=0.013). The corresponding findings for nursing students were 5.1 ± 4.8 mm (first year) and 5.2 ± 5.4 mm (last year) (p=0.464). On the average, the students scored 56.05% correct answers on the questionnaire. A difference in knowledge was observed between pre-clinical students (34.13%) and interns/trainees (69.75%). Our findings highlight the importance of conducting regular Mantoux testing on healthcare students and implementing biosafety measures and permanent education on TB for future healthcare professionals.